Pathogenic bacteria profile in the mineral waters sold in Brazil: a panorama of 2010 and 2019 (Brazilian Journal of Health Research, 2022)
Introduction: Despite of the increase in the demand for mineral water (MW) in Brazil, it does not always have the adequate quality for human consumption, since it can be contaminated by pathogens. Objectives: Conduct a systematic literature review about the pathogenic bacteria (PB) profile in MW market in Brazil. Methods: Original articles published between 2010 and 2019 in Scielo, PUBMED and/or LILACS were selected, using the following descriptors in Health Sciences: “Mineral water”, “bacteria”, “pathogens”, “microbial control” and “Brazil”, and Borealian logistics “AND” and “OR”. Results: Thirteen articles described the PB contamination in at least one of the samples analyzed, and among the 381 samples evaluated, 51.5% were positive for these microorganisms. In addition, in some cases, there was an overlap of bacteria, and the most described pathogens were total coliforms (13/3 articles) and fecal coliforms (12/13 articles). However, in percentage, the most prevalent were total coliforms (30.2% of the samples) and Pseudomonas aeruginosa (22.8% of the samples). Discussion: The high rate of pathogenic bacteria in MW samples described in the literature represents a risk to consumer health, as it is a trigger for the occurrence of numerous pathologies. Conclusion: It is necessary to reassess the current legislation and better inspection of mineral water produced and sold in Brazil, since, although there is a legislation establishing the maximum acceptable limits for microorganisms, the literature reports that there is a high rate of contamination by pathogenic bacteria. Therefore, unfit for sale and human consumption.
Keywords: Microorganisms; Coliforms; Pseudomonas aeruginosa